Кореляційна схема кадрової синхронізації у системах зв'язку з QPSK-модуляцією - Sadchenko, A. V.; Kushnirenko, O. A.; Yefimov, O. I.; Punko, V. V.; Parovyi, S. Y. (PE "Politekhperiodika", Book and Journal Publishers, 2017)
The information efficiency of communication systems using quadrature amplitude modulation is reduced because of the costs for data transmission necessary to provide frame synchronization and the required time to search for the sync signal and to go into the tracking mode of the synchronization system.One of the most effective schemes of constructing a frame synchronization system is the correlation diagram. In order for this diagram to operate, signal-code constructions with good aperiodic autocorrelation properties are required.The aim of this study is to develop an effective frame synchronization system for quadrature modulation communication systems based on binary signal-code sequences with an ideal sectioned non-periodic autocorrelation function.In this paper, we propose a frame synchronization scheme for QPSK modulation based on binary sequences of even length with an ideal autocorrelation function. All binary synchronous sequences of length N = 8 with the idealness of the autocorrelation function are analytically found in the study. On the basis of the chart of the code distance spectrum in the Hamming metric for binary sequences of N = 8 length, it was established that such sequences have a correcting ability that allows correcting single errors. Based on the structural properties of binary sequences of N = 8 length, sequences of a larger multiple length (N = 16, N = 32, etc.) can be synthesized.The practical value of the proposed scheme of frame synchronization is to reduce the complexity of technical implementation and increase the overall noise immunity of the communication system. The proposed approach can be successfully used to synchronize communication systems with QAM modulation with a large number of signal positions such as QAM 16, QAM 64, etc.